2015
DOI: 10.4187/respcare.03663
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Rehabilitation in COPD: Effect of 2 Aerobic Exercise Intensities on Subject-Centered Outcomes—A Randomized Controlled Trial

Abstract: BACKGROUND: Exercise training is an important component of pulmonary rehabilitation, but it remains questionable how training intensity affects patient-centered outcomes. The aim of this study was to compare the effects of 2 aerobic training intensities on health-related quality of life (HRQOL), symptom control, and exercise tolerance in subjects with COPD. METHODS: Thirtyfour subjects with mild to very severe COPD participated in an equivalence/non-inferiority randomized controlled trial with a parallel group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 46 publications
(51 reference statements)
0
31
0
Order By: Relevance
“…While both groups significantly improved cycle endurance time and quality of life, there were no between‐group differences, except for a significantly greater improvement in the symptom score in the home training group. In the most recent study of patients with moderate COPD (FEV 1 ≈ 55% predicted), exercise training at 80% W peak ( n = 17) was compared with 60% W peak ( n = 17) . All participants were trained, supervised, three times per week for 30 min and, according to patient preference, on either a treadmill (76% of participants) or cycle ergometer (24% of participants).…”
Section: Intensity Of Exercise Training: Studies In Copd Patientsmentioning
confidence: 99%
See 2 more Smart Citations
“…While both groups significantly improved cycle endurance time and quality of life, there were no between‐group differences, except for a significantly greater improvement in the symptom score in the home training group. In the most recent study of patients with moderate COPD (FEV 1 ≈ 55% predicted), exercise training at 80% W peak ( n = 17) was compared with 60% W peak ( n = 17) . All participants were trained, supervised, three times per week for 30 min and, according to patient preference, on either a treadmill (76% of participants) or cycle ergometer (24% of participants).…”
Section: Intensity Of Exercise Training: Studies In Copd Patientsmentioning
confidence: 99%
“…While the study by Casaburi et al . provides some evidence that a higher training intensity elicits greater physiological outcomes, the larger and more recent studies of Maltais et al and Santos et al concur with the lack of a dose–response in physiological outcomes to exercise intensity in healthy older subjects . Based on the evidence available, it is doubtful that higher training intensities improve patient‐centred outcomes, such as quality of life, any more than lower intensity training.…”
Section: Intensity Of Exercise Training: Studies In Copd Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…All studies found that pulmonary rehabilitation programs or individual physical therapy programs were effective in improving the quality of life [12][13][14][15][16][17], physical endurance [12][13][14][15][16][18][19][20][21][22][23], respiratory muscle strength [13,18,23], reducing symptoms of CoPd [14,16,19,23], improving the function of external breathing [16,[24][25][26], blood parameters [22,27], cognitive functions [21], functional state of muscles [28], survival rates [29,30], and reducing the number of hospital days [31]. The main part of investigations was devoted to the comparison of therapeutic rehabilitation programs that included several components and referred to stable patients with CoPd.…”
Section: Resultsmentioning
confidence: 99%
“…In patients with COPD, there are studies comparing the physiological benefits of different endurance training intensities [7,8,9], within or across different exercise training modalities (continuous vs. interval training) [10,11,12]. The optimal training intensity that is tolerable by the majority of patients and that yields the greatest physiological benefits is still unclear [13].…”
Section: Introductionmentioning
confidence: 99%